Normal pressure hydrocephalus: Increase of utricular input in responders to spinal tap test. Issue 5 (May 2016) - Böttcher, N.; Bremova, T.; Feil, K.; Heinze, C.; Schniepp, R.; Strupp, M.
Highlights: One third of patients with normal pressure hydrocephalus had impaired otolith function. Patients with an increase of walking velocity after spinal tap test only had a significant increase of oVEMP amplitude. Otolith dysfunction may contribute to imbalance in normal pressure hydrocephalus (NPH) and increased utricular function after spinal tap test may be relevant for gait improvement. Abstract: Objective: To investigate whether there is a change in ocular (oVEMP) and cervical (cVEMP) vestibular evoked myogenic potentials in patients with normal pressure hydrocephalus (NPH) before and after spinal tap test (STT). Methods: In 25 patients (6 females, age 62–83 years) c/oVEMP were measured before and after STT. Patients with an increase of >20% of walking velocity were classified as responders ( n = 10). VEMP were also measured in a control group of 13 non-NPH patients. Results: All patients had reproducible oVEMP; 68% had cVEMP. There was a significant increase of the peak-to-peak (pp) oVEMP amplitude after STT in responders (8.5 ± 2.7 to 18.9 ± 7.5 μV ( p = 0.010)). No significant changes were found in non-responders (13.4 ± 7.6 to 15.3 ± 8.6 μV) or controls (12.4 ± 7.6 to 12.5 ± 6.8 μV). There were no significant differences in cVEMP before and after spinal tap test (STT). Conclusion: One third of patients with suspected NPH had impaired otolith function. Responders to STT only had a significant increase of oVEMP and thereby utricular input, probably due to a decrease of pressure. Significance: Both findings indicate that otolith dysfunction may contribute to imbalance in NPH and that increased utricular function after STT may be relevant for gait improvement.